Haematological changes associated with Newcastle disease vaccination in chickens using gums from Cedrela odorata and Khaya senegalensis as delivery agents (Nigerian Journal of Physiological Sciences, 2020)
Our previous ex-vivo and in vivo investigations have established immunopotentiating property of Khaya senegalensis and Cedrela odorata gums; however the safety of the use of this gum combination in chicken has not been described. Hence this study evaluates the haematological profile of chickens vaccinated with Newcastle disease vaccine delivered through the oral and ocular routes using gums from Cedrela odorata and Khaya senegalensis as delivery agents. 252 one-day old chickens were grouped gum-vaccine oral (GVOR), vaccine oral (VOR), gum-vaccine ocular (GVOC), vaccine ocular (VOC), gum oral (GOR), gum ocular (GOC), no-gum-no-vaccine but challenged (NGNV/C), no-gum-no-vaccine unchallenged (NGNV/U). They were vaccinated on days 21 and 42 and challenged day 84. Blood samples were collected before first vaccination and at selected intervals afterwards. Analysis was done using one way ANOVA with P0.05) throughout the period of observation across groups with no observable derangements. Hence, the absence of derangement in haematological indices from this study suggests that the dilution rate recommended from the ex-vivo study is safe for administration of Newcastle disease vaccine in chickens irrespective of the routes of delivery